Relationship between Compliance in Implementing Patient Admission SOPs and Nurse Performance in Inpatient Rooms - Laily, Eka Isranil; Tarigan, Almina Rospitaria; Saragih, Nurlela Petra; Sucahyo, Dedek (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2025)
Implementing nursing care SOP in the inpatient room is essential in achieving a superior and quality hospital. The service's success can be the basis for developing a health strategy depending on the participation of nurses to increase compliance because, until now, nursing care has been provided in the presence of nurses, especially in patient management (patient admission SOP). This study aimed to determine the relationship between nurse compliance in implementing patient admission SOPs and nurse performance in the inpatient room of RSU DR. GL Tanjung Morawa Medan. This research method uses descriptive correlation and a cross-sectional design—data collection through questionnaires. The population is 30 people. The sampling technique is Total Sampling. The data analysis used is Univariate and Bivariate, obtained in the frequency distribution table, and Bivariate analysis using the Chi-Square test. The results showed that most nurses complied with implementing SOPs as much as 66.7%, and the majority of nurse performance was classified as 50%. The chi-square test results showed a p-value of 0.02; there was a significant relationship between nurse compliance in implementing patient admission SOPs and nurse performance in the inpatient room of DR. GL Tobing Tanjung Morawa Hospital.